HUBUNGAN LAMA KERJA DAN KEBISINGAN DENGAN STRES KERJA PADA PEKERJA UNIT PRODUKSI PAVING BLOCK DI UD. RIZKI ASSILA ULFA LUBUK PAKAM KABUPATEN DELI SERDANG - Anggi Isnani Parinduri; Luci Riani Br Ginting; Irmayani Irmayani; Risa Elvira Prabaja (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2020)
In line with current industrial growth which requires labor as the dominant element that manages raw materials, machinery, equipment and other processes in the workplace. Each workplace contains a variety of potential hazards that can affect the health of the workforce or can cause occupational diseases that are work stress. The purpose of this study is to describe the relationship between work duration and noise and work stress in paving block production unit workers at UD. Rizki Assila Ulfa Lubuk Pakam Deli Serdang Regency 2020. This research uses analytical descriptive method using cross sectional design. The population in this study were 30 paving block production unit workers with the sampling technique using Total Sampling. Data analysis was performed univariately and bivariately using the Chi-Square statistical test with Î± = 0.05. The results of the analysis show that there is a relationship between work duration and noise with work stress on paving block production unit workers at UD. Rizki Assila Ulfa Lubuk Pakam Deli Serdang Regency in 2020, namely the length of work p value (0.005) <Î± (0.05), and noise p value (0.031) < Î± (0.05). Based on the results of research it is recommended to workers that workers condemn personal protection by using Personal Protective Equipment (PPE) such as ear plugs that can protect the ears from noise caused by machines, so as to reduce exposure to noise that can interfere with health.